Relationship between Chemical Composition and Nematicidal Activity of Different Essential Oils - D’Addabbo, Trifone (Plants (Basel), 2020)
In this study, the relationship between nematicidal activity and chemical composition of ten essential oils (EOs) from different plant species was investigated both in in vitro assays on juveniles (J2) and eggs of the root-knot nematode Meloidogyne incognita and in experiments on tomato in soil infested by M. incognita. Nematode J2 were exposed for 4, 8 or 24 h to 0.78–100 μg mL(−1) concentrations of each EO, whereas 24, 48 or 96 h exposures to 250, 500 and 1000 μg mL(−1) solutions were tested on M. incognita egg masses. Treatments with 50, 100 or 200 μg kg soil rates of each EO were applied in the experiment on potted tomato. The highest nematicidal potential resulted for the C. verum EO, as highly toxic to both M. incognita J2 and eggs and strongly suppressive on nematode multiplication on tomato roots. The infestation of M. incognita on tomato roots was also strongly reduced by the EOs from E. citriodora and S. aromaticum, both highly toxic to M. incognita J2 but less active on nematode eggs. Adversely, R. graveolens EO strongly inhibited the egg hatch but was limitedly toxic to the infective J2. Chemical composition of the EOs was determined by GC-FID and GC-MS. The ten EOs showed a very different chemical composition in terms of major phytochemicals, with one or two dominant components totally amounting up to 85%. The structure–activity relationship based on the main phytochemicals identified in the assayed EOs and their nematicidal effects on M. incognita was also discussed. Results from this study confirmed that the selection of suitable EO raw materials can lead to the formulation on new effective nematicidal products.